Cross-sectional and prospective inter-relationships between depressive symptoms, vascular disease and cognition in older adults. Issue 13 (29th October 2018) - Mewton, Louise; Reppermund, Simone; Crawford, John; Bunce, David; Wen, Wei; Sachdev, Perminder
Abstract: Background: It has been proposed that vascular disease is the mechanism linking depression and cognition, but prospective studies have not supported this hypothesis. This study aims to investigate the inter-relationships between depressive symptoms, cognition and cerebrovascular disease using a well-characterised prospective cohort. Method: Data came from waves 1 (2005–2007) and 2 (2007–2009) of the Sydney Memory and Ageing Study ( n = 462; mean age = 78.3 years). Results: At wave 1, there was an association between depressive symptoms and white matter hyperintensity (WMH) volume [ b = 0.016, t (414) = 2.34, p = 0.020]. Both depressive symptoms [ b = −0.058, t (413) = −2.64, p = 0.009] and WMH volume [ b = −0.011, t (413) = −3.77, p < 0.001], but not stroke/transient ischaemic attack (TIA) [ b = −0.328, t (413) = −1.90, p = 0.058], were independently associated with lower cognition. Prospectively, cerebrovascular disease was not found to predict increasing depressive symptoms [stroke/TIA: b = −0.349, t (374.7) = −0.76, p = 0.448; WMH volume: b = 0.007, t (376.3) = 0.875, p = 0.382]. Depressive symptoms predicted increasing WMH severity [ b = 0.012, t (265.9) = −3.291, p = 0.001], but not incident stroke/TIA (odds ratio = 0.995; CI 0.949–1.043; p = 0.820). When examined in separate models, depressive symptoms [ b = −0.027, t (373.5) = −2.16, p = 0.032] and a history of stroke/TIA [ b = −0.460, t (361.2) = −4.45, p < 0.001], but not WMH volume [ b = 0.001, t (362.3) = −0.520, p = 0.603], predicted declines in cognition. When investigated in a combined model, a history of stroke/TIA remained a predictor of cognitive decline [ b = −0.443, t (360.6) = −4.28, p < 0.001], whilst depressive symptoms did not [ b = −0.012, t (359.7) = −0.96, p = 0.336]. Conclusions: This study is contrasted with previous prospective studies which indicate that depressive symptoms predict cognitive decline independently of vascular disease. Future research should focus on further exploring the vascular mechanisms underpinning the relationship between depressive symptoms and cognition.